2017
DOI: 10.1007/s00404-017-4605-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in birth-related pain perception impact of neurobiological and psycho-social factors

Abstract: Pain sensitivity showed a decrease when comparing post-partum with prepartum values. The extent and direction of CPM appear to be a trait variable that predicted post-partum hypalgesia without being changed itself. Post-partum hypalgesia was reduced in women with a history of abuse and high trait anxiety, which suggests that individual differences in CPM affect childbirth experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…While experimental CPM correlated with delivery-induced PPT changes in the CG, in line with earlier results, 9 we now found that this correlation broke down in the TG. While the deficit in pain inhibition in maltreated women is small, it may be a marker of relevant dysfunction and deserves further investigation.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…While experimental CPM correlated with delivery-induced PPT changes in the CG, in line with earlier results, 9 we now found that this correlation broke down in the TG. While the deficit in pain inhibition in maltreated women is small, it may be a marker of relevant dysfunction and deserves further investigation.…”
Section: Discussionsupporting
confidence: 92%
“…Cold pressor test was administered on the nondominant hand to avoid segmental interaction. The chosen test sites are outside of common pain areas such as the back, allow for a direct comparison with Berlit et al, 9 and are considered to yield the most reliable CPM results. 78 To reduce confusion and nervousness, participants were introduced to the equipment and associated stimuli (except for ice water) before testing.…”
Section: Quantitative Sensory Assessmentsmentioning
confidence: 99%
See 3 more Smart Citations